The Influence of Product Awareness and Value Perception on Innovation Performance: A Case Study in Mineral Water Company - Yugowati Praharsi; Gaguk Suhardjito (International Journal of Supply Chain Management, 2019)
This paper explores the influence of consumers product awareness, value perception, and trust in helping innovation performance of mineral water company. In order to clarify the relationships among these constructs, a structural equation model (SEM) is employed to examine the model fit and the three hypotheses. The results show that consumers product awareness and value perception is critical due to its influence on the consumers trust. The consumers trust exhibits a positive influence on the innovation performance. The research supports the existence of a more complex that the consumers trust partially mediates the relationships between product awareness and innovation performance. Moreover, the consumers trust also partially mediates the relationships between value perception and innovation performance. This study can enhance the innovation performance of mineral water company to achieve sustainable competitive advantage.